Assessing the Engagement Strategies of Indonesia’s Top 5 Universities on Instagram - Akbari, Deni Adha; Rochaety , Eti; Wulan, Mulyaning; Purwandari, Diah; Adji, Fanina (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
This research aims to assess the engagement strategies of Indonesia's top 5 universities on Instagram, analyzing how these strategies enhance interaction with the audience. Utilizing a combination of content analysis and machine learning, the study scrutinizes various elements like posting frequency, content type, and usage of hashtags. The findings reveal that strategic content placement, emotional appeal, and the incorporation of interactive elements significantly bolster engagement. These strategies are particularly effective in fostering a vibrant academic community and enhancing the universities' outreach efforts. This study contributes to the understanding of digital engagement in higher education and offers actionable insights for optimizing social media marketing strategies.